2019
DOI: 10.1186/s12864-019-5934-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping and profiling of γH2AX binding hotspots in response to different replication stress inducers

Abstract: Background: Replication stress (RS) gives rise to DNA damage that threatens genome stability. RS can originate from different sources that stall replication by diverse mechanisms. However, the mechanism underlying how different types of RS contribute to genome instability is unclear, in part due to the poor understanding of the distribution and characteristics of damage sites induced by different RS mechanisms. Results: We use ChIP-seq to map γH2AX binding sites genome-wide caused by aphidicolin (APH), hydroxy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 73 publications
3
13
1
Order By: Relevance
“…Induction of DNA damage in these cells via an HU pulse led to the spread of γH2AX over wide areas (purple histogram and, cf. Fig 1D , panel 3), as previously characterized by others for γH2AX induction [ 26 , 31 ], and consistent with previously published findings during MVM infection [ 21 ]. NS1 broadly relocalized to the γH2AX domains in both analyses (blue histogram).…”
Section: Resultssupporting
confidence: 92%
“…Induction of DNA damage in these cells via an HU pulse led to the spread of γH2AX over wide areas (purple histogram and, cf. Fig 1D , panel 3), as previously characterized by others for γH2AX induction [ 26 , 31 ], and consistent with previously published findings during MVM infection [ 21 ]. NS1 broadly relocalized to the γH2AX domains in both analyses (blue histogram).…”
Section: Resultssupporting
confidence: 92%
“…We therefore asked whether this concentration of HU destabilizes CFSs. In agreement with previous reports 51, 52 , we observed breaks in metaphase chromosomes, part of them at CFSs. However, we found that only a subset of the Aph-sensitive CFSs displays breaks in HU, and at far lower frequency than in Aph.…”
Section: Discussionsupporting
confidence: 93%
“…It has been proposed that CFS instability results from fork barriers raised by sequences prone to form secondary structures 18,19,36 . At least four types of observations argue against this model: (i) analysis of the nucleotide sequence of several FISH-mapped CFSs has provided contrasting results regarding the presence of such roadblocks at a substantial proportion of the sites 37 .…”
Section: Discussionmentioning
confidence: 99%